Active and reactive energy storage STATCOM distribution system power management - Albanna, Enaam; Al-Karakchi, Ahmed A. Abdullah; Al-Rifaie, Alya H. (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
One of the critical factors influencing the overall development of modern power systems is the control of active and reactive power flows in distribution power systems. The static synchronous compensator (STATCOM) with storage energy is a powerful device that can control active and reactive power flow in a distribution system. A simulation model of power management using STATCOM with energy storage is presented in this paper. A fuzzy logic controller is proposed to manage the powers. The simulation results demonstrate STATCOM's ability to manage the active and reactive power flow in a controlled distribution line, and thus the powers regulated between feeders, by utilizing storage energy.